ANALISIS IMPLIKASI ADAT YANG DI LANGGAR TERKAIT DENGAN PELANGGARAN HAK ASASI MANUSIA MENURUT HUKUM ADAT NUSA TENGGARA TIMUR (KABUPATEN SUMBA) - Khalik Salim, Idgham; Svinarky, Irene (SCIENTIA JOURNAL, 2024)
Indonesia is a country with diverse ethnicities, cultures and customs. Each tribe has customary law toregulate the behavior of its people, such as Sumba Island with the customary law of Piti Maranggangu(arrest marriage). Arrest marriage is a process where a woman is taken by force to become a wife. Theaim of this research is to determine whether customary criminal cases can be linked to Indonesian positivelaw in terms of human rights violations. Normative legal research is used by the author as a type ofresearch in this research to explain Customary law that lives in society is unwritten law, and lives in themidst of traditional society which is inherited from ancestors. The nature of the research used isdescriptive. The discussion in this research is the application of the customary law of marriage andcapture which is a living tradition in society which is rseflected in their patterns of action in accordance withtheir customs and socio-cultural patterns. In the 1945 Constitution, Article 18B section (2) emphasizes therecognition and respect for the unity of customary law communities and their rights by the state as long asthey are in line with the constitution, but in reality there are still customary laws whose customarysanctions violate the constitution and also violate human rights based on Law Number 39 of 1999concerning Human Rights.